The masculine form in grammatically gendered languages and its multiple interpretations: a challenge for our cognitive system. (January 2021) - Gygax, Pascal; Sato, Sayaka; Öttl, Anton; Gabriel, Ute
Abstract: We analyze the semantic ambiguity of the grammatically masculine form in languages where this form has more than one meaning (e.g., French, German, English to some extent) when used to refer to human beings. We discuss this ambiguity in terms of inference processing, meaning activation, and the link between language and the way we perceive reality. Importantly, we attempt to identify and explain the cognitive mechanisms at the very heart of gender biases when readers (and speakers) construct mental representations of gender through language. We ground our argument in memory-based approaches to reading, the meaning activation selection model and the thinking-for-speaking hypothesis. This paper provides a cognitive perspective to understanding why, in grammatical gender languages, gender representations are male biased. Highlights: We present a paper on the cognitive mechanisms involved when processing the masculine grammatical form. We argue that the specific meaning of the masculine form is more likely to be activated, as it is dominant. We frame the dominance of the specific meaning of the masculine form in terms of meaning saliency. We argue that the dominance of the specific meaning of the masculine form feeds our androcentric society.